Revision of the genus Tulipa L. (Liliaceae) in Turkey - Eker İsmai̇l; Babaç Mehmet Teki̇n; Koyuncu, Mehmet (Phytotaxa, 2014)
To address taxonomic problems stemming from treatments in the Flora of Turkey and other publications, Tulipa is revised for Turkey. Following detailed morphological and cytotaxonomic studies of the taxa, Tulipa in Turkey has been found to be represented by 17 species, two subspecies and two varieties (in total 19 taxa). A new key for the species and detailed descriptions of taxa are provided, as are synonyms and typification as far as possible, distribution, habitat types, localities and conservation status of all taxa. These studies are based on approximately 1000 fresh and 2000 herbarium specimens. Adopting the classification of Van Raamsdonk & De Vries, Tulipa is divided into two subgenera, Eriostemones and Tulipa, which were previously treated as sections by Marais in Flora of Turkey following Boissier’s classification. Tulipa subgenus Eriostemones is divided into two sections following Baker’s treatment: Sylvestres and Saxatiles. However, section Sylvestres is again divided into two subsections following Baker and Hall’s treatments: Sylvestres and Biflores (here described). Section Saxatiles is further divided into three subsections, with the addition of two new subsections: Saxatiles, Orphanidetes and Humiles. The type subgenus Tulipa is divided into two sections: Tulipa and Clusianae. In subsection Humiles, T. pulchella is accepted at species rank, having usually been placed as a synonym of T. humilis. Some previously uncollected species (T. raddii and T. saxatilis) and a doubtful record (T. clusiana), after the first collection of material in Turkey, have been recollected and verified.